Expression of HIF1α in intestinal epithelium restricts arthritis inflammation by inhibiting RIPK3-induced cell death machinery - Lyu, Pang; Wen, Jinming; Zhang, Wenshuo; Liu, Ning; Stolzer, Iris; Gießl, Andreas; Jia, Yewei; Mauro, Daniele; Zhang, Fulin; Ciccia, Francesco; Soulat, Didier; Günther, Claudia; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives: To investigate the mechanism by which intestinal epithelial cell (IEC) death induces arthritis. Methods: IEC death was assessed by staining for necroptosis and apoptosis markers and fluorescence in situ hybridisation at different time points during collagen-induced arthritis (CIA). During the development of CIA, messenger RNA (mRNA) sequencing was performed, followed by Gene Ontology enrichment analysis of differentially expressed genes. Mice deficient for hypoxia-inducible factor 1α (Hif1a) in IECs (Hif1aΔIEC) were generated and induced for arthritis. mRNA sequencing, chromatin immunoprecipitated (ChIP) DNA sequencing and ChIP-qualitative PCR were performed on IECs from Hif1aΔIEC mice and littermate controls. Effects of HIF1α stabilisation by inhibition of prolyl hydroxylase domain-containing enzymes and treatment with the inhibitor of receptor-interacting protein kinase-3 (RIPK3) were tested in intestinal organoids and in CIA. Results: IEC underwent apoptotic and necroptotic cell death at the onset of arthritis, leading to impaired gut barrier function. HIF1α was identified as one of the most upregulated genes in IECs during the onset of arthritis. Deletion of Hif1a in IEC enhanced IEC necroptosis, triggered intestinal inflammation and exacerbated arthritis. HIF1α was found to be a key transcriptional repressor for the necroptosis-inducing factor RIPK3. Enhanced RIPK3 expression, indicating necroptosis, was also found in the intestinal epithelium of patients with new-onset rheumatoid arthritis. Therapeutic stabilisation of HIF1α as well as small-molecule-based RIPK3 inhibition rescued intestinal necroptosis in vitro and in vivo and suppressed the development of arthritis. Conclusion: Our results identify IEC necroptosis as a critical link between the gut and the development of arthritis.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Arthritis; Experimental; Arthritis; Rheumatoid; Immune System Diseases; Inflammation

Hypoxia-immune-related microenvironment prognostic signature for osteosarcoma - Zhang, Wenshuo; Lyu, Pang; Andreev, Darja; Jia, Yewei; Zhang, Fulin; Bozec, Aline (Frontiers in Cell and Developmental Biology, 2022)
Introduction: Increasing evidences have shown that hypoxia and the immune microenvironment play vital roles in the development of osteosarcoma. However, reliable gene signatures based on the combination of hypoxia and the immune status for prognostic prediction of osteosarcoma have so far not been identified. Methods: The individual hypoxia and immune status of osteosarcoma patients were identified with transcriptomic profiles of a training cohort from the TARGET database using ssGSEA and ESTIMATE algorithms, respectively. Lasso regression and stepwise Cox regression were performed to develop a hypoxia-immune-based gene signature. An independent cohort from the GEO database was used for external validation. Finally, a nomogram was constructed based on the gene signature and clinical features to improve the risk stratification and to quantify the risk assessment for individual patients. Results: Hypoxia and the immune status were significantly associated with the prognosis of osteosarcoma patients. Seven hypoxia- and immune-related genes (BNIP3, SLC38A5, SLC5A3, CKMT2, S100A3, CXCL11 and PGM1) were identified to be involved in our prognostic signature. In the training cohort, the prognostic signature discriminated high-risk patients with osteosarcoma. The hypoxia-immune-based gene signature proved to be a stable and predictive method as determined in different datasets and subgroups of patients. Furthermore, a nomogram based on the prognostic signature was generated to optimize the risk stratification and to quantify the risk assessment. Similar results were validated in an independent GEO cohort, confirming the stability and reliability of the prognostic signature. Conclusion: The hypoxia-immune-based prognostic signature might contribute to the optimization of risk stratification for survival and personalized management of osteosarcoma patients.
CRIS-Team WoS Importer:2023-01-13

Osteocytes support bone metastasis of melanoma cells by CXCL5 - Jia, Yewei; Zhang, Fulin; Meng, Xianyi; Andreev, Darja; Lyu, Pang; Zhang, Wenshuo; Lai, Chaobo; Schett, Georg; Bozec, Aline (Cancer Letters, 2024)
Bone metastasis is a common complication of certain cancers such as melanoma. The spreading of cancer cells into the bone is supported by changes in the bone marrow environment. The specific role of osteocytes in this process is yet to be defined. By RNA-seq and chemokines screening we show that osteocytes release the chemokine CXCL5 when they are exposed to melanoma cells. Osteocytes-mediated CXCL5 secretion enhanced the migratory and invasive behaviour of melanoma cells. When the expression of the CXCL5 receptor, CXCR2, was down-regulated in melanoma cells in vitro, we observed a significant decrease in melanoma cell migration in response to osteocytes. Furthermore, melanoma cells with down-regulated CXCR2 expression showed less bone metastasis and less bone loss in the bone metastasis model in vivo. Furthermore, when simultaneously down-regulating CXCL5 in osteocytes and CXCR2 in melanoma cells, melanoma progression was abrogated in vivo. In summary, these data suggest a significant role of osteocytes in bone metastasis of melanoma, which is mediated through the CXCL5-CXCR2 pathway.
CRIS-Team Scopus Importer:2024-04-26